Suspected Short Peripheral Venous Catheter Intravascular Embolization: Identification and Management - Rodriguez, Limael Esteban; Rodriguez, Francisco Steven; Rodriguez-Pedrogo, Francisco Javier (International Journal of Cardiovascular Practice, 2018)
Embolization of a standard short peripheral venous catheters (S-PVC) related to catheter fracture is an extremely rare complication. Early identification and management is essential to avoid potential complications (i.e. central embolization, arrhythmias, cardiorespiratory failure, etc.). In this report, we describe a case of suspected short-PVC fracture in a pediatric patient. The goal is to review available literature and provide insight on what to do in the setting of suspected PVC fracture.